“A Comprehensive Examination Of Translation Techniques Based On Materials: Analysing The Translation Methods Used For The English Rendition Of Chinese Empty Words” (Cuestiones de Fisioterapia, 2023)
This work is being driven by the goal of enhancing translation techniques for translating illogical chinese into english. The aim from the beginning was to compile a collection of significant works authored by writers from both china and the united kingdom. Finding out how translators deal with empty words is the goal of this corpus, which was created for that reason. It is necessary to follow eight distinct procedures in order to get a translation that is of high quality. These phases include matching, editing, sharing, implication, grammatical travel, borrowing, and omission (mismatch). A discrepancy is addressed in the seventh phase. According to the specialists, a significant evolution has taken place in the field of grammatical conveyure. A determination will be made on the degree to which certain procedures and non-procedures, such as shared matching and loaning, have been implemented as the inquiry continues to develop. Additionally, it seems that this inquiry has yielded a number of significant outcomes, such as the translation of chinese empty words into english and the prospect of discovering two other patterns that are remarkable. This research unquestionably marks a big improvement in the field, since no previous study has attempted to compile a list of all of the empty terms that are used by chinese translators. The researchers came to the conclusion that the most difficult sentence types were those that relate to empty phrases. One kind of sentence that was included was an adverbial sentence. Platitudes, in a nutshell, are not nearly as difficult to comprehend as was previously believed, which is contrary to what individuals who have held opinions for a long time may now believe.